Study of advanced in-space propulsion technologies - Tan, De Jun (2017)
The main obstacle in achieving fast transit between earth and deep space destinations is not the launch, but travelling through space itself. As much as we like to explore our universe to find other habitable planets and learn more about it in general, the lack of reliable advanced in-space propulsion technologies which can provide the necessary velocities makes it difficult to achieve. The focus on improving existing chemical propulsion systems has also contributed to the slow progress of developing advanced in-space propulsion technologies. In order for deep space exploration missions to be meaningful, they must be able to reach their destination and transmit data back to earth in a reasonable amount of time.